The Role of UTAUT2 in Understanding Technology Adoption: A Study of the Merdeka Mengajar Platform Among Indonesian Teachers - Siti Aminah; Addin Aditya; Yekti Asmoro Kanthi (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2024)
This research investigates the adoption of the Merdeka Mengajar application using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. The study aims to identify the factors influencing teachers' behavioral intentions and usage behavior regarding this educational technology platform. A total of 383 teachers from various levels in Malang were sampled from a broader population of 8,936. Statistical analysis uses SEM (Structural Equation Modelling) analysis techniques. The findings suggest that performance expectancy, effort expectancy, social influence, hedonic motivation, and price value significantly influence behavioral intention. However, facilitating conditions and habit do not show a direct significant impact on use behavior. These results indicate that while technological support such as infrastructure and internet access is necessary, it alone may not be enough to motivate consistent usage without internal factors like perceived usefulness or enjoyment of the app. Moreover, the habitual use of new technology may require additional support and time before it can significantly affect behavior. This study contributes valuable insights into the adoption of educational technologies, especially in the Indonesian context, where digital learning platforms are increasingly being integrated into teaching practices. Future research may explore how ongoing support and user experience improvements can further enhance the app's adoption.